2018
DOI: 10.1364/boe.9.002588
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous monitoring of cerebral perfusion and cytochrome c oxidase by combining broadband near-infrared spectroscopy and diffuse correlation spectroscopy

Abstract: Preterm infants born with very low birth weights are at a high risk of brain injury, in part because the premature brain is believed to be prone to periods of low cerebral blood flow (CBF). Tissue damage is likely to occur if reduction in CBF is sufficient to impair cerebral energy metabolism for extended periods. Therefore, a neuromonitoring method that can detect reductions in CBF, large enough to affect metabolism, could alert the neonatal intensive care team before injury occurs. In this report, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 41 publications
4
40
0
Order By: Relevance
“…It has been shown that this can be done by a broadband CW-NIRS system. 54 However, this relies on a more complex calibration scheme and as all continuous-wave methods are more prone to influences of external light. Consequently, this is often used to measure baseline optical properties and it relies on Beer-Lambert law for measuring change from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that this can be done by a broadband CW-NIRS system. 54 However, this relies on a more complex calibration scheme and as all continuous-wave methods are more prone to influences of external light. Consequently, this is often used to measure baseline optical properties and it relies on Beer-Lambert law for measuring change from baseline.…”
Section: Resultsmentioning
confidence: 99%
“…B-NIRS and DCS can also be combined, as recently demonstrated. 79 We also recommend measuring systemic physiological changes in parallel, based on the systemic-physiology-augmented fNIRS neuroimaging approach recently introduced by us. 80,81 Especially the measurement of stimulus-evoked systemic blood pressure changes might be of particular interest.…”
Section: Implications Of Our Study For Future Functional Near-infrarementioning
confidence: 99%
“…This study was done in a piglet model of neonatal hypoxia-ischemia (HI). The results demonstrate that simultaneous neuromonitoring of perfusion and metabolism could provide vital alerts of brain injury, especially in preterm infants born [129].…”
Section: Animal Studiesmentioning
confidence: 85%